A city shaped by diplomacy - Dirk van Gameren; Anteneh Tesfaye Tola (ABE Journal)
Ethiopia is an old country with a long history of political change, both domestically and towards the rest of the world. Internally, Ethiopia’s ever-changing socio-political behavior was manifested by a tradition of relocating its seat of government. Axum, Lalibela, Teguelat, Gondar, Magdala, Ankober, and Mekele are only a few examples of such temporary headquarters, and many other “roving capitals” are excluded.1 The most recent shift was the foundation of the current capital city Addis Ababa in 1886. In the 131 years since then, this city has evolved from a simple village of hot springs and encampments into a global diplomatic center. The city’s diplomatic relevance has grown especially rapidly since 1950. Today, it hosts continental and global institutions such as the African Union (AU), a number of United Nation institutions (UN-ECA, UNDP, UNESCO) and others, in addition to diplomatic institutions for bilateral relations. Until today, Addis Ababa contains only fragments of the disruption caused by the brief period of Italian occupation between 1936 and 1941, when the occupiers attempted to erase the existing city and build a new colonial capital. This paper looks at the evolution of Addis Ababa through the agency of diplomacy. It focuses on the morphological and architectural manifestations of diplomacy in the city, based on a timeline of five recognizable periods. Using exemplary cases, it illustrates the physical and spatial impact and architectural influences associated with diplomacy and diplomatic institutions. Subsequently, we argue that the emergence of Addis Ababa as a diplomatic center in its first couple of decades anchored it as a lasting political center, while the diplomatic developments that followed and their physical manifestations played a vivid formative role in the city’s urbanization. Within Addis Ababa’s poly-nuclear structure, the diplomatic institutions prevail as frames and points of reference, spread out over the whole city.